2016
DOI: 10.20307/nps.2016.22.2.87
|View full text |Cite
|
Sign up to set email alerts
|

Tea Flavonoids Induced Differentiation of Peripheral Blood-derived Mononuclear Cells into Peripheral Blood-derived Endothelial Progenitor Cells and Suppressed Intracellular Reactive Oxygen Species Level of Peripheral Blood-derived Endothelial Progenitor Cells

Abstract: − Endothelial dysfunction in atherosclerosis is associated with increasing oxidative stress that could be reversed by antioxidant. Therefore epigallocatechin gallate (EGCG), epicatechin gallate (ECG), epigallocatechin (EGC) and catechin (C) of tea flavonoids were investigated for their roles in regenerating endothelial cell. Peripheral blood mononuclear cells (PB-MNCs) were isolated, plated and cultured in medium with/without treatment of EGCG, ECG, EGC and C. Results showed that among all EGCG, ECG, EGC and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…32 Later, it was found that EGCG, ECG, EGC and C of tea extract could induce differentiation of peripheral blood mononuclear cells (PB-MNCs) into peripheral blood-derived EPCs (PBEPCs). 31 The resulted PB-EPCs were confirmed by flow cytometry to detect EPCs membrane markers expressions (CD34, CD133, VEGFR-2). Treatment of EGCG, ECG, EGC and C increased the percentages of all CD34, CD133, VEGFR-2 expressions.…”
Section: Tea Extractmentioning
confidence: 96%
See 3 more Smart Citations
“…32 Later, it was found that EGCG, ECG, EGC and C of tea extract could induce differentiation of peripheral blood mononuclear cells (PB-MNCs) into peripheral blood-derived EPCs (PBEPCs). 31 The resulted PB-EPCs were confirmed by flow cytometry to detect EPCs membrane markers expressions (CD34, CD133, VEGFR-2). Treatment of EGCG, ECG, EGC and C increased the percentages of all CD34, CD133, VEGFR-2 expressions.…”
Section: Tea Extractmentioning
confidence: 96%
“…Herbal extracts were now highly investigated due to its potential to induce cell proliferation. [31][32][33][34] The following are some potential herbal extracts in inducing stem cell proliferation.…”
Section: B I O P H a R M A C E U T I C A L I N S T I T U T Ementioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies showed that several antioxidants could improve EPCs growth and stem cells differentiation into EPCs [10,11]. Impaired proliferation of EPCs in cardiovascular-related disease was also able to be enhanced with antioxidant treatment [12,13].…”
Section: Introductionmentioning
confidence: 98%